A high-nickel cobalt-free positive electrode material and its preparation method and application
By covering the surface of the high-nickel positive electrode material with nano-level ultra-low thermal conductivity and uniformly dispersed coating with disc nest mill, the safety hazards caused by heat release of high-nickel positive electrode material are solved, and the effect of improving safety performance is achieved.
Patent Information
- Application Number
- CN202310488118.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-27
AI Technical Summary
In the high-nixel positive electrode material has a high deliquency state, due to the de-liquification of oxygen ions, resulting in the destruction of the lattice structure, deterioration of the circulation performance, and accompanied by a large amount of heat release, which poses a safety hazard.
The nano-level ultra-low thermal conductivity cladding material is coated with lithium nickel manganate material, and uniformly dispersed and coated through dish nest mill to reduce heat transfer on the surface of the material and improve the safety performance of the positive electrode material.
It significantly improves the DSC temperature of the positive electrode material, reduces the maximum heat exogenous value and total heat exogenous, and improves the safety performance of high-nickel cobalt-free positive electrode material.
Smart Images

Figure CN116470037B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a high-nickel cobalt-free positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in various fields such as electronics, automobiles, and aerospace due to their high energy density and good cycle performance. As people have higher and higher requirements for the environmental protection, endurance, and life of lithium-ion batteries, battery design and optimization are becoming more and more important. As the core of lithium-ion batteries, the performance of the positive electrode material directly determines the performance of the battery. As people's requirements for the range of electric vehicles become higher and higher, high nickel will continue to grow into the mainstream technology for long-range models; with the development of related technologies and the integration of vehicle platform functions, new energy vehicles will continue to develop towards higher energy density and longer range in the future, and the development trend of high-nickel lithium batteries will become more and more obvious.
[0003] However, as the nickel content in the positive electrode material increases, the battery capacity increases while also causing a series of safety problems; due to the overlap of energy bands between nickel and oxygen, under high lithium removal conditions, oxygen will escape from the lattice, destroying the lattice structure and causing poor cycle performance, accompanied by the release of a large amount of heat, posing a safety hazard.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a high-nickel cobalt-free positive electrode material. In view of the safety hazard caused by heat release of high-nickel positive electrode materials in the prior art, the present invention coats and modifies the cobalt-free layered positive electrode material, and coats a class of nanomaterials with ultra-low thermal conductivity on the surface of the lithium nickel manganese oxide material to reduce heat transfer on the surface of the material, significantly increase the DSC temperature of the pole piece made of the positive electrode material, reduce the maximum heat release value and the total heat release, thereby improving the safety performance of the high-nickel cobalt-free positive electrode material.
[0006] The second object of the present invention is to provide a method for preparing the high-nickel cobalt-free positive electrode material, which avoids defects such as uneven coating or agglomeration of coating materials that may be caused by conventional dry coating or wet coating by using a disc nest mill for dispersion coating.
[0007] The third object of the present invention is to provide an application of the high-nickel cobalt-free positive electrode material.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A high-nickel cobalt-free positive electrode material, comprising lithium nickel manganese oxide and a coating layer uniformly coated on the lithium nickel manganese oxide; the general formula of the lithium nickel manganese oxide is Li a Ni b Mn c Zr d O2, wherein 0.9≤a≤1.3, 0.5≤b<1, 0.001≤d≤0.01, b+c+d=1; the general formula of the coating layer is XCuZrY3, wherein X includes at least one of Rb or Cs, and Y includes at least one of S, Se or Te.
[0010] Preferably, in the general formula of the lithium nickel manganese oxide, 1.02≤a≤1.15, 0.7≤b<1, 0.002≤d≤0.006.
[0011] Preferably, the lithium nickel manganese oxide is made of single crystal material, the median particle size of the lithium nickel manganese oxide is 2.0 μm to 5.0 μm, and the specific surface area of the lithium nickel manganese oxide is 0.4 m 2 / g~0.8m 2 / g.
[0012] Preferably, the median particle size of the coating layer is ≤400 nm.
[0013] The preparation method of the high-nickel cobalt-free positive electrode material comprises the following steps: step 1, uniformly dispersing the coating layer material on the surface of the lithium nickel manganese oxide material through a disc mill to form a coating layer and obtain a positive electrode material precursor; step 2, calcining the precursor material at a high temperature to obtain a coated high-nickel cobalt-free positive electrode material.
[0014] Preferably, in step 1, the coating layer material is mixed with a solvent to obtain a slurry, and the slurry after grinding is transported to a disc nest mill and evenly dispersed on the surface of the lithium nickel manganese oxide material;
[0015] More preferably, the solvent is deionized water;
[0016] More preferably, in the slurry, the mass ratio of the coating material to the solvent is 1:(1-2);
[0017] More preferably, the linear speed of the grinding process is 10 m / s to 15 m / s, and the time of the grinding process is 1 h to 5 h;
[0018] More preferably, the grinding medium is zirconium beads, and the particle size of the zirconium beads is 0.2 mm to 0.5 mm;
[0019] More preferably, the mass ratio of the slurry to the lithium nickel manganese oxide material is 0.5% to 5%.
[0020] Preferably, in step 1, the air intake of the disc mill is 1250m 3 / h~4000m 3 / h, and the spray pressure of the disc mill is 0.5MPa-0.8MPa.
[0021] Preferably, in step 1, the feed temperature of the lithium nickel manganese oxide material is 200° C. to 300° C., and the rotation speed of the lithium nickel manganese oxide material is 4500 rpm to 6000 rpm.
[0022] Preferably, in step 2, the temperature of the high temperature calcination is 300° C. to 500° C., and the time of the high temperature calcination is 3 h to 8 h.
[0023] The uses of the high-nickel cobalt-free positive electrode material in the field of lithium-ion batteries include but are not limited to: a battery positive electrode made based on the high-nickel cobalt-free positive electrode material, or other composite positive electrode materials or battery positive electrodes including the high-nickel cobalt-free positive electrode material, or a lithium-ion battery made with the high-nickel cobalt-free positive electrode material, or an electrical component or electrical appliance made with the high-nickel cobalt-free positive electrode material.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] First, the present invention adopts a nano-scale ultra-low thermal conductivity coating layer material to achieve the goal of improving the battery capacity with a high nickel positive electrode material while avoiding the potential safety hazard caused by heat release; the positive electrode material treated with the coating layer of the present invention is tested by differential scanning calorimetry after use, and has the advantages of high DSC temperature, low maximum heat release value and low total heat release.
[0026] Second, the present invention adopts a disc nest mill for coating operation, disperses the positive electrode material through a high-speed rotating mechanical structure, and fully disperses the solid powder through the airflow impulse of a unique nested vortex; at the same time, the coating material is introduced into the disc nest mill in the form of a slurry and transported into the vortex in the form of a spray, at which time the high-temperature positive electrode material contacts the spray and evaporates the liquid phase to form a uniform coating; the process is simple and effective, and the coating uniformity is excellent, and it is particularly suitable for the cobalt-free high-nickel lithium nickel manganese oxide positive electrode material of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1The DSC spectrum of Example 1 of the present invention is provided. DETAILED DESCRIPTION
[0029] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] The present invention is carried out through the following specific implementation methods: a high-nickel cobalt-free positive electrode material, the components of which include lithium nickel manganese oxide and a coating layer uniformly coated on the outside of the lithium nickel manganese oxide; the general formula of the lithium nickel manganese oxide is Li a Ni b Mn c Zr d O2, wherein 0.9≤a≤1.3, 0.5≤b<1, 0.001≤d≤0.01, b+c+d=1; the general formula of the coating layer is XCuZrY3, wherein X includes at least one of Rb or Cs, and Y includes at least one of S, Se or Te.
[0031] The high-nickel cobalt-free positive electrode material described in the present invention does not contain the cobalt element. On the one hand, when the coating process under the specific components of the present invention is aimed at cobalt-containing (or high-cobalt) positive electrode materials, the thermal insulation effect of the ultra-low thermal conductivity coating layer is not obvious; on the other hand, low-cobalt or cobalt-free is the current research and development trend of positive electrode materials, and it also has lower costs.
[0032] As a preferred embodiment, in the general formula of the lithium nickel manganese oxide, the value of a includes but is not limited to 1.02, 1.04, 1.06, 1.08, 1.1, 1.12, 1.14, 1.15; the value of b includes but is not limited to 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.98; the value of d includes but is not limited to 0.002, 0.003, 0.004, 0.005, 0.006.
[0033] As a preferred embodiment, in the coated high-nickel cobalt-free positive electrode material, the mass ratio of the lithium nickel manganese oxide to the coating layer is 100:(0.1-1).
[0034] The preparation method of the coated high-nickel cobalt-free positive electrode material comprises the following steps: step 1, uniformly dispersing the coating layer material on the surface of the lithium nickel manganese oxide material through a disc nest mill to form a coating layer and obtain a positive electrode material precursor; step 2, calcining the precursor material at a high temperature to obtain a coated high-nickel cobalt-free positive electrode material.
[0035] Disc Nest Mill is a new type of device that integrates drying, crushing and modification. It can process various forms of materials in pure solid and solid-liquid mixed states, and has the advantages of energy saving, environmental protection, simple process, etc. The material is carried into the drying chamber by the carrier gas with set temperature and dried. The specially designed impeller in the chamber and a large number of discs placed in different positions rotate at high speed to form multiple nested swirls. The impact force, friction force and shear force of the airflow quickly disperse the material evenly and highly evenly.
[0036] Experiments have found that the nano-scale ultra-low thermal conductivity coating material used in the present invention has a serious agglomeration phenomenon, and dry coating often cannot evenly coat the coating material on the surface of the cobalt-free high-nickel positive electrode material; at the same time, since the cobalt-free high-nickel positive electrode material is a single crystal positive electrode material, pure wet coating will cause agglomeration of the positive electrode material during spraying, affecting the particle size and electrical properties of the positive electrode material. When the disc nest mill is used to control the droplet size of the coating material spray, when the droplets come into contact with the cobalt-free high-nickel positive electrode material with a higher surface temperature, the water in the coating material slurry evaporates, and the nano-scale coating material remains on the surface of the positive electrode material, and the coating is tight and not easy to fall off.
[0037] As a preferred embodiment, in step 1, the coating material is mixed with a solvent to obtain a slurry, and the ground slurry is transported to a disc nest mill and evenly dispersed on the surface of the lithium nickel manganese oxide material to form a coating layer and obtain a positive electrode material precursor; as a more preferred embodiment, the coating material with a D50 of less than 400nm is obtained by grinding the slurry, and further, the linear speed of the grinding process includes but is not limited to 10, 11, 12, 13, 14, 15 (unit: m / s), and the grinding time includes but is not limited to 1, 2, 3, 4, 5 (unit: h); as a more preferred embodiment, the grinding medium is zirconium beads, and the particle size of the zirconium beads is but is not limited to 0.2, 0.3, 0.4, 0.5 (unit: mm). As a more preferred embodiment, the mass ratio of the slurry to the lithium nickel manganese oxide material includes but is not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%.
[0038] As a preferred embodiment, in step 1, the air intake of the disc mill includes but is not limited to 1250, 1280, 1300, 1350, 1400, 1500, 2000, 2500, 3000, 3500, 3800, 4000 (unit: m 3 / h), the spray pressure of the disc nest mill includes but is not limited to 0.5, 0.6, 0.7, 0.8 (unit: MPa); the feed temperature of the lithium nickel manganese oxide material includes but is not limited to 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300 (unit: ° C), and the rotation speed of the lithium nickel manganese oxide material includes but is not limited to 4500, 4800, 5000, 5200, 5400, 5600, 5800, 6000 (unit: rpm).
[0039] As a preferred embodiment, in step 2, the temperature of the high-temperature calcination includes but is not limited to 300, 320, 340, 360, 380, 400, 420, 440, 460, 480, 500 (unit: ° C), and the time of the high-temperature calcination includes but is not limited to 3, 4, 5, 6, 7, 8 (unit h).
[0040] Example 1
[0041] (1) Preparation of basic layered single crystal cathode material Li 1.08 Ni 0.85 Mn 0.146 Zr 0.004 O2, D50 is 3.5um, specific surface area is 0.58m 2 / g; RbCuZrTe3 and deionized water were stirred in a mass ratio of 1:1, and then put into a sand mill for sand grinding. The medium used was 0.3 mm zirconium beads, the grinding line speed was 14 m / s, and the grinding was performed for 3 h. After grinding, the D50 was 258 nm.
[0042] (2) The disc nest mill is preheated. When the feed port temperature reaches 300°C, the nano slurry obtained in (1) and the basic layered positive electrode material are simultaneously fed into the disc nest mill. The nano slurry feed rate is 4 kg / h, the spray pressure is 0.7 MPa, and the basic layered positive electrode material feed rate is 200 kg / h, thereby obtaining a cobalt-free positive electrode material with a surface coated with an ultra-low thermal conductivity nanomaterial.
[0043] (3) The cobalt-free positive electrode material obtained in (2) was calcined at 350° C. for 4 h in an oxygen atmosphere to obtain the finished positive electrode material of this embodiment.
[0044] Example 2
[0045] It is basically the same as Example 1, except that RbCuZrTe3 is replaced by RbCuZrSe3.
[0046] Example 3
[0047] It is basically the same as Example 1, except that RbCuZrTe3 is replaced by CsCuZrS3.
[0048] Example 4
[0049] It is basically the same as Example 1, except that: Li 1.08 Ni 0.85 Mn 0.146 Zr 0.004 O2 replaced by Li 1.02 Ni 0.7 Mn 0.298 Zr 0.002 O2.
[0050] Example 5
[0051] It is basically the same as Example 1, except that: Li 1.08 Ni 0.85 Mn 0.146 Zr 0.004 O2 replaced by Li 1.15 Ni 0.95 Mn 0.044 Zr 0.006 O2.
[0052] Example 6
[0053] It is basically the same as Example 1, except that the nano slurry feed rate of 4 kg / h is replaced by 8 kg / h.
[0054] Comparative Example 1
[0055] It is basically the same as Example 1, except that the RbCuZrTe3 coating and the operations involved are eliminated.
[0056] Comparative Example 2
[0057] The method is basically the same as Example 1, except that: (2) the whole process is replaced by using a high-speed mixer for coating and stirring at 2000 rpm for 20 minutes.
[0058] Comparative Example 3
[0059] It is basically the same as Example 1, except that the spray pressure of 0.7 MPa is replaced by 0.2 MPa.
[0060] Test example
[0061] The positive electrode materials obtained in the examples and comparative examples, carbon black (SP), and polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 92:4:4, mixed evenly, and coated on a 20 μm thick aluminum foil, dried at 100°C for 4 h, cut into positive electrode sheets with a diameter of 12 mm, and then rolled to obtain a sheet with a surface density of 9 g / cm 2 , compacted density is 3.3g / cm 3 ; A lithium sheet (16 cm in diameter) was used as the negative electrode, assembled into a button half-battery, left to stand for 12 h, and charged at a rate of 0.1C until the voltage reached 4.3 V; left to stand for 5 minutes, then discharged at 0.1C until the voltage reached 3 V, left to stand for 5 minutes, and then charged at a rate of 0.1C until the voltage reached 4.3 V.
[0062] Disassemble the fully charged button cell, take out the positive electrode, soak it in NMP for 2 hours, take out the electrode, dry it, drop it into the electrolyte and put it into the test device. The maximum heat release value and the corresponding temperature can be accurately determined by the differential scanning calorimetry (DSC) curve, and the total heat released by the corresponding change can also be quantitatively calculated. Test conditions: heat up from 25℃ to 350℃ at a heating rate of 5K / min, and introduce nitrogen at a rate of 50mL / min.
[0063] Figure 1 The DSC spectrum obtained from the test in Example 1 is given.
[0064] Table 1
[0065] DSC temperature (℃) DSC maximum calorific value (mW / mg) DSC total calorific value (J / g) Example 1 213.62 2.22 317.06 Example 2 212.85 2.12 337.04 Example 3 209.94 2.98 342.11 Example 4 211.21 2.21 319.76 Example 5 209.59 2.54 351.45 Example 6 208.64 2.65 365.24 Comparative Example 1 198.57 17.98 519.91 Comparative Example 2 203.28 9.85 485.34 Comparative Example 3 201.32 10.56 504.36
[0066] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A high-nickel cobalt-free positive electrode material, characterized in that: It comprises lithium nickel manganese oxide and a coating layer uniformly coated on the lithium nickel manganese oxide; The general formula of the lithium nickel manganese oxide is Li a Ni b Mn c Zr d O2, wherein 0.9≤a≤1.3, 0.5≤b<1, 0.001≤d≤0.01, b+c+d=1; the general formula of the coating layer is XCuZrY3, wherein X includes at least one of Rb or Cs, and Y includes at least one of S, Se or Te.
2. The high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: In the general formula of the lithium nickel manganese oxide, 1.02≤a≤1.15, 0.7≤b<1, 0.002≤d≤0.
006.
3. The high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The median particle size of the lithium nickel manganese oxide is 2.0 μm to 5.0 μm, and the specific surface area of the lithium nickel manganese oxide is 0.4 m 2 / g~0.8m 2 / g; And / or, the median particle size of the coating layer is ≤400nm.
4. The method for preparing a high-nickel cobalt-free positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: Step 1: uniformly dispersing the coating material onto the surface of the lithium nickel manganese oxide material through a disc mill to form a coating layer and obtain a positive electrode material precursor; Step 2: calcining the precursor material at high temperature to obtain a coated high-nickel cobalt-free positive electrode material; wherein the temperature of the high-temperature calcination is 300°C~500°C.
5. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 4, characterized in that: In step 1, the coating layer material is mixed with a solvent to obtain a slurry, and the slurry after grinding is transported to a disc nest mill and evenly dispersed on the surface of the lithium nickel manganese oxide material.
6. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 5, characterized in that: The solvent is at least one of deionized water, ethanol or acetone.
7. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 5, characterized in that: In the slurry, the mass ratio of the coating layer material to the solvent is 1:(1-2).
8. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 5, characterized in that: The linear speed of the grinding process is 10m / s to 15m / s, and the time of the grinding process is 1h to 5h.
9. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 5, characterized in that: The grinding medium is zirconium beads, and the particle size of the zirconium beads is 0.2 mm to 0.5 mm.
10. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 5, characterized in that: The mass ratio of the slurry to the lithium nickel manganese oxide material is 0.5% to 5%.
11. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 4, characterized in that: In step 1, the air intake of the disc mill is 1250m 3 / h~4000m 3 / h, and the spray pressure of the disc mill is 0.5MPa~0.8MPa.
12. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 4, characterized in that: In step 1, the feed temperature of the lithium nickel manganese oxide material is 200° C. to 300° C., and the rotation speed of the lithium nickel manganese oxide material is 4500 rpm to 6000 rpm.
13. The method for preparing a high-nickel cobalt-free positive electrode material according to claim 4, characterized in that: In step 2, the high temperature calcination time is 3h~8h.
14. Use of the high-nickel cobalt-free positive electrode material according to any one of claims 1 to 3 in the field of lithium-ion batteries.
Citation Information
Patent Citations
Coating method of lithium ion battery cathode material
CN108767232A
Preparation method of lanthanum zirconate in-situ coated high-nickel ternary cathode material
CN109461917A